Digital Technology’s Implementation in Hybrid Learning at Higher Educational Level - Monica Fransisca; Permata Saputri, Renny (The Indonesian Journal of Computer Science, 2023)
The majority of sectors are currently influenced by digital technology, including the education sector. Through the development of digital technology, a new learning model can be designed, namely hybrid learning. Hybrid learning can help the learning process, such as providing variations in learning, minimizing space and time limitations, and improving digital skills. Hybrid learning is a solution in higher education that has limited learning space but has facilities for implementing digital technology in hybrid learning. The research subjects were 36 students of educational informatics engineering department. The research method used was research and development, with ADDIE model (Analysis, Design, Develop, Implementation, and Evaluation). At the implementation stage, an effectiveness test was carried out to see the extent to which the application of digital technology in hybrid learning had an effect on the learning process. The research’s results were the implementation of digital hybrid learning technology which consists of combination face-to-face classes with e-learning moodle. Another result from this research was the value of effectiveness was obtained, which is 86.44% conducted from 36 subjects and was categorized as very effective for implementation in higher educational level.